Safety and immunogenicity of meningococcal ACWY CRM(197)-conjugate vaccine in children, adolescents and adults in Russia - Ilyina, Natalia (Hum Vaccin Immunother, 2014)
Neisseria meningitidis is the leading cause of bacterial invasive infections in people aged <15 years in the Russian Federation. The aim of this phase III, multicenter, open-label study was to assess the immunogenicity and safety of the quadrivalent meningococcal CRM(197-)conjugate vaccine MenACWY when administered to healthy Russian subjects aged 2 years and above. A total of 197 subjects were immunized with a single dose of the vaccine, and serogroup-specific serum bactericidal activity was measured pre and 1-month post-vaccination with human complement (hSBA) serum titers. Regardless of baseline serostatus, 1 month after a single dose of MenACWY-CRM(197) 85% (95%CI, 79–90%) of subjects showed serologic response against serogroup A, 74% (67–80%) against serogroup C, 60% (53–67%) against serogroup W, and 83% (77–88%) against serogroup Y. The percentage of subjects with hSBA titers ≥ 1:8 1 month after vaccination was 89% (83–93%) against serogroup A, 84% (78–89%) against serogroup C, 97% (93–99%) against serogroup W, and 88% (82–92%) against serogroup Y. Comparable results were obtained across all subjects: children (2 to 10 years), adolescents (11 to 17 years), and adults (≥18 years). The MenACWY-CRM(197) vaccine showed an acceptable safety profile and was well tolerated across all age groups, with no serious adverse events or deaths reported during the study. In conclusion, a single dose of meningococcal MenACWY-CRM(197) vaccine is immunogenic and has an acceptable safety profile, provides a broad protection against the most frequent epidemic serogroups, and is a suitable alternative to currently available unconjugated monovalent or bivalent polysaccharide vaccines in Russia.